2014
DOI: 10.1175/jhm-d-13-091.1
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Hysteresis in Snow Depletion Curves to Improve the Water Budget of a Land Surface Model in an Alpine Catchment

Abstract: To cite this version:Claire Magand, Agnès Ducharne, Nicolas Le Moine, Simon Gascoin. Introducing hysteresis in snow depletion curves to improve the water budget of a land surface model in an Alpine catchment. Journal of Hydrometeorology, American Meteorological Society, 2014, 15 (2) ), located in the French Alps, generates 10% of French hydropower and provides drinking water to 3 million people. The Catchment land surface model (CLSM), a distributed land surface model (LSM) with a multilayer, physically based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 49 publications
1
46
0
3
Order By: Relevance
“…5 for the case of the SD). This result is interesting because it reflects the hysteresis in the relationship between the amount of snow on the ground and its extent, which was often observed in alpine catchments (e.g., Magand et al, 2014). Small snow depths can cover large areas during the accumulation period.…”
Section: In Situ Data Vs Modis Productsmentioning
confidence: 58%
“…5 for the case of the SD). This result is interesting because it reflects the hysteresis in the relationship between the amount of snow on the ground and its extent, which was often observed in alpine catchments (e.g., Magand et al, 2014). Small snow depths can cover large areas during the accumulation period.…”
Section: In Situ Data Vs Modis Productsmentioning
confidence: 58%
“…In spring, the SWE is systematically overestimated except over the Lena, whose seasonal cycle is well reproduced by ORCHIDEE-MICT. This corresponds to an excessive persistence of the snow cover, which may be explained by the absence of hysteresis in the snow depletion curve relating the snow cover extent and the SWE (e.g., Magand et al, 2014). In the Yenisei and Mackenzie basins, the SWE in winter is closer to observations with the GSWP3 forcing, with the exception of springtime values, which are better under CRUNCEP forcing.…”
Section: Snow-related Processes Controlling Land Water Storage In Thementioning
confidence: 90%
“…Snow density generally increases with the increasing of snow age. We know that there is in fact a hysteresis in the relationship between snow water equivalent and snow depth (Magand et al, 2014): during accumulation days, snowfall occurs all over the catchment, and the mean snow depth tends to increase quickly and uniformly over the catchment. By contrast, during the ablation days, snowmelt tends to occur in preferential locations due to variability of topography and vegetation in the catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Singh and Kumar (1996) and Singh et al (2000) demonstrated a seasonal decrease of DDF S with increasing albedo due to seasonal changes of land surface characteristics. Spatial variations of basin topography, such as elevation, terrain slope, aspect and terrain shading change the spatial energy conditions for snowmelt and lead to significant variations of DDF S (Marsh et al, 2012;Bormann et al, 2014). Generally, regions with a large contribution of sensible heat flux to the heat balance tend to have low degree-day factors (Hock, 2003).…”
Section: Z H He Et Al: Estimating Degree-day Factors From Modis Fomentioning
confidence: 99%